Suffering for water: infrastructure, household access and its fluid negotiations in peri-urban Tamale, Ghana - Ngben, Joseph Mborijah (Department of Environmental and Geographical Science, 2020)
Analysis of access to water in the global South tends to disproportionately focus on the presence of water infrastructure such as the piped network to estimate the proportion of population that have access to water. While interest in access to water has advanced considerably, less research has focused on practices, strategies and experiences of everyday water access. This study engages with this issue in two neighborhoods, Kpanvo and Katariga, in Tamale, Ghana, exploring the ways in which residents negotiate to access water services in practice. Through participant observations and in-depth interviews, the study sets out to address three specific objectives, namely to understand how households experience and describe water access; to explore the various strategies and infrastructures households mobilise to gain and maintain access to water; and to examine the factors that mediate households’ water access. Water infrastructure in the study neighbourhoods includes pipes, but critically also other sources of water (dams, boreholes and wells) and storage infrastructure (underground reservoirs, poly tanks, plastic drums, metal drums, earthen ware pots, aluminium pots and jerry cans) where residents store water for use during periods of interruptions of supplies. Also given that water is not always readily available in the private homes of residents, vehicles such as tanker trucks, bicycles, motorbikes and motorised tricycles are used to haul water from various sources, making them part of water infrastructure that make water flow in and to the neighbourhoods. Similarly, humans themselves, particularly women and girls, are a part of the infrastructure that make water flow as they carry water from both improved and unimproved sources to meet households water needs. Findings from the study demonstrate that continuous access to water, even if a household is directly connected to a piped water system, is impossible due to practices of water rationing, contrary to a normative assumption of universal and reliable water service provisioning associated with networked water supply. Household access to water is constructed through multiple strategies and infrastructures, mediated as much by access to financial resources as by networks of social relationships. Affluent households are able to acquire household connections, and some, a priori rejected connections to the pipe network due to erratic supply, in favour of the more expensive options of installation of mechanised boreholes and buying water from tanker operators. In contrast, poor households leveraged networks of social relationships to enter into tap sharing arrangements with neighbours on agreed conditions of payment of monthly service bills or gifts of water from owners of private water sources. Building on Anand (2011) and Peloso and Morinville (2014) this thesis therefore concludes that the way in which access to water needs to be understood is not simply in terms of access to pipes - as critical as they are - but also in terms of the strategies and negotiations that structure and are embedded in practices through which access to water is gained, maintained and potentially controlled at the household and neighbourhood level. Analysing access to water in this way makes visible the various ways that humans shape water infrastructure and water access.